Applying Kolb`s theory of experiential learning to coach education - Stirling, A. E. (Journal of Coaching Education, 2013)
Coach education is the key to improved coaching. In order for coach education initiatives to be effective though, the conceptualization of those initiatives must be developed based on empirical learning theory. It is suggested that Kolb`s theory of experiential learning may be an appropriate learning theory to apply to coach education. This paper outlines how Kolb`s theory of experiential learning was used in the development of Canada`s National Coaching Certification Program coach education module entitled "Empower +: Creating Positive and Healthy Sport Experiences." The module is summarized briefly, and Kolb`s six key tenets of experiential learning are reviewed. Applications of each tenet within the coach education module are highlighted, and recommendations are made for future evaluation and research.